DIGITAL TRANSFORMATION IN DESIGN AND THE IMPACT OF MODERN TOOLS AND TECHNOLOGIES - Almnshdawy Hussain Abdualee; Karrar Hayder Mohammed (Global Prosperity, 2024)
Design is undergoing a profound transformation, driven by the rapid evolution of digital tools and technologies. This “digital transformation” is impacting almost every aspect of the design landscape, from the way humans ideate and collaborate to the tools humans use and the products create. Powerful software like Figma, Sketch, and Adobe XD are revolutionizing design workflows. These tools offer collaborative features, real-time prototyping, and integrations with other platforms, fostering agility and efficiency. In this case digital fashion, as a new field of design based on the use of 3D technologies in the processes of designing, visualizing, distributing, and marketing products, is becoming an integral part of the practice of contemporary digital transformation spreading. The purpose of the article is to analyze the trajectory of the evolution of digital transformation and characterize its impact on the transformative processes of culture. The methodological basis of the study is a systematic approach to analyzing the formation of the phenomenon of digital transformation using a historiographical analysis of the development of tools for digitalizing. The material for the historiographical and cultural analysis is a wide range of sources from scientometric databases. The process of formation and development of digital transformation is represented by three stages. For the first time, the markers characterizing the stages of digital transformation development are identified, which are the socio-technical indicators of the digital platform. Digitalization in this paper is considered as a transformation that leads to the expansion of the influence of the digital system on its own functionality and on the socio-cultural sphere. The processes of digitalization are presented in the form of internal and external professional factors in the form of hardware platform, software, workflows, operating models, competencies and acquired skills of the new generation of designers. The technical and sociocultural perspective of digitalization depends on internal sociotechnical factors and is determined by the scale of modelling the virtual social environment for installation. Understanding the peculiarities of the formation, history of development and socio-cultural role of digital transformation in design will help to increase the reliability of the assessment of its contribution to the sustainable development of culture